The Effect of a Disaster Nursing Education Program on Nurses' Preparedness for Responding to Probable Natural Disasters - Ghanbari V; Maddah S.S; Khankeh HR; Karimloo M; Ardalan.A (Iran University of Medical Sciences, 2011)
Background & Aims: Nurses, as the pioneers of healthcare in societies, play an important role before, during, and after disasters. Enhancement of their professional skills for the purpose of helping the injured is one of the basic principles in health management in accidents and disasters. The aim of this study is to investigate the effects of a disaster nursing education program on the improvement of nurses' preparedness.   Material & Methods: It was a quasi-experimental, single group study. The sample including 113 nurses working in Razi psychiatric hospital were selected by census and asked to fill out the "preparedness for confronting disasters" questionnaire, which was developed by the authors. The preparedness program, which consisted of a one-day workshop on disaster management, top-table maneuver, and an operational maneuver, were performed for the participants. The preparedness of all participating nurses was measured one week and also one month after the program. Data were analyzed ANOVA for repeated measures by SPSS-PC (v.17).   Results: Our results showed that the mean scores of knowledge, attitude, and performance improved from 5.55 to 19.88, from 66.18 to 72.41, and from 3.36 to 12.48, respectively in pretest and follow up measurements, which indicated a statistically significant difference (p<0.001). In addition, the mean score for total preparedness was increased from 75.14 in pretest to 104.77 in follow up, which is statistically significant (p<0.001)   Conclusions: According to the findings in order to promote and maintain the preparedness of nursing staff, inclusion of disaster programs in their academic educational curriculum and as a continued educational program is recommended.